Measuring User Acceptance Of The Accurate-5 Application Using The Technology Acceptance Model (TAM) And Smartpls Software: Case Study Of Students Of State Senior High School 1 Lembang Bandung - Hasanah Tisna Amijaya; Adjat Sudarjat (JURNAL COMPUTECH & BISNIS, 2026)
This study employed the Technology Adoption Model (TAM) to evaluate students' utilization of the Accurate-5 accounting software at SMA Negeri 1 Lembang, Bandung. The study aims to evaluate user satisfaction levels and determine the influencing factors. The study utilizes Perceived Usefulness (PU) and Perceived Ease of Use (PE) as independent variables, Behavioral Intention to Use (BIU) as a mediating variable, and Actual System Use (AU) as the dependent variable. The researcher employed SmartPLS version 4 to analyze and assess the data. The results demonstrate enhanced reliability and validity, as evidenced by high Cronbach's alphas and composite validity scores, with an Average Variance Extracted (AVE) exceeding 0.5. Hypothesis testing using P-values demonstrates that Perceived Ease of Use significantly influences Behavioral Intention to Use (P < 0.05$). Conversely, Perceived Usefulness exerts no significant influence on Behavioral Intention to Use (P > 0.05$). Furthermore, Behavioral Intention to Use significantly influences Actual System Use (P < 0.05$). Based on T-statistics and P-values, Perceived Usefulness directly affects Actual System Use (T > 1.96, P < 0.05$), whereas Perceived Ease of Use does not exert a direct influence (T < 1.96, P > 0.05$).